Title: The Role of E-Management in the Development of Higher Education Institutions (Economic studies journal, 2023)
This study aims to explore the level of utilization of electronic management in higher education institutions in their administrative, educational, and office aspects, and evaluate its role in the development of higher education institutions. The study was conducted on students from the Faculty of Economics and Political Science at Misurata University, and an electronic questionnaire containing 26 items related to the research variables was distributed. A total of 124 questionnaires were analyzed, and through statistical analysis, several key findings were obtained. The study revealed that the studied educational institution utilizes electronic management at a low level in its administrative, educational, and office dimensions. Additionally, the study demonstrated a statistically significant relationship between electronic management and the development of higher education institutions.
Keywords: Electonic management; electronic administrative process; E-educational administration, office electronic administration; Develop higher education institutions